2021
DOI: 10.1002/mas.21727
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the compound class and functional groups in protonated analytes via diagnostic gas‐phase ion‐molecule reactions

Abstract: Diagnostic gas‐phase ion‐molecule reactions serve as a powerful alternative to collision‐activated dissociation for the structural elucidation of analytes when using tandem mass spectrometry. The use of such ion‐molecule reactions has been demonstrated to provide a robust tool for the identification of specific functional groups in unknown ionized analytes, differentiation of isomeric ions, and classification of unknown ions into different compound classes. During the past several years, considerable efforts h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 68 publications
(211 reference statements)
0
21
0
Order By: Relevance
“…[T3-H] − and [rT3-H] − were mass analyzed in the cell of an FT-ICR, which allowed measurement of the accurate mass of the anions, obtaining an m /z value of 649.78319 with a mass error of 0.66 ppm with respect to the exact mass of the formula [C 15 H 11 NO 4 I 3 ] − (649.78276 Da). [T3-H] − and [rT3-H] − were allowed to react with selected neutral molecules with appropriate volatility aiming to substantiate the different deprotonation sites of the two anions, possibly enabling characteristic ion-molecule reactions. , In this regard, Kenttämaa et al showed diethylmethoxyborane (DEMB) to react selectively with the phenolate functionality, producing the DEMB adduct, while carboxylate groups showed no reactivity . Based on this evidence, both [T3-H] − and [rT3-H] − were mass isolated and stored in the presence of DEMB introduced at a stationary pressure of 10 –7 mbar.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[T3-H] − and [rT3-H] − were mass analyzed in the cell of an FT-ICR, which allowed measurement of the accurate mass of the anions, obtaining an m /z value of 649.78319 with a mass error of 0.66 ppm with respect to the exact mass of the formula [C 15 H 11 NO 4 I 3 ] − (649.78276 Da). [T3-H] − and [rT3-H] − were allowed to react with selected neutral molecules with appropriate volatility aiming to substantiate the different deprotonation sites of the two anions, possibly enabling characteristic ion-molecule reactions. , In this regard, Kenttämaa et al showed diethylmethoxyborane (DEMB) to react selectively with the phenolate functionality, producing the DEMB adduct, while carboxylate groups showed no reactivity . Based on this evidence, both [T3-H] − and [rT3-H] − were mass isolated and stored in the presence of DEMB introduced at a stationary pressure of 10 –7 mbar.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, the obtained drift times were correlated with the CCS of the two isomers. 48 The so-obtained CCS values are reported in Table 1 and 67,68 In this regard, Kenttamaa et al showed diethylmethoxyborane (DEMB) to react selectively with the phenolate functionality, producing the DEMB adduct, while carboxylate groups showed no reactivity. 42 Based on this evidence, both [T3-H] − and [rT3-H] − were mass isolated and stored in the presence of DEMB introduced at a stationary pressure of 10 −7 mbar.…”
Section: ■ Introductionmentioning
confidence: 99%
“…In some cases, these isomers differ from each other by carrying different functional groups that are connected to the backbone of the molecules in different ways; therefore, they tend to exhibit different reactivities toward a certain reagent. Diagnostic gas-phase ion-molecule reactions have been discovered to aid the identification of different functional groups, and they have been successfully coupled to LC-MS. Further CID experiments on the product ions of the ion-molecule reactions have also been carried out for more detailed structural elucidation of various molecules [ 4 , 61 , 62 ]. A more detailed description of its applications will be introduced in Section 3 .…”
Section: Technical Advances In Ms-based Structural Elucidation Techni...mentioning
confidence: 99%
“…A combination of several different mass analyzers (hybrid instruments) has enabled more accurate mass and structural analysis [ 3 ]. Several mass spectrometers also serve as chambers for performing gas-phase reactions so that additional structural information can be obtained when fragment ions of the analyte are not informative enough to elucidate the precursor’s structure (see Section 2.4 and Section 2.5 , and examples in Section 3 ) [ 4 , 5 , 6 ]. Some highly reactive intermediates, that are not easy to capture in the condensed phase, can also be studied in the gas phase using MS, thus providing more insight into understanding the behavior of these “uncommon” species and how they may participate in critical chemical and biological processes [ 7 , 8 , 9 , 10 , 11 ].…”
Section: Introduction To Mass Spectrometry and Overviewmentioning
confidence: 99%
“…On the other hand, MS 2 based on diagnostic gas-phase ion-molecule reactions can often be used to successfully identify different functional groups in previously unknown, protonated analytes, including N-oxide, carbamate, sulfone, and sulfoxide functional groups. 20 In this study, the utility of both of the above MS 2 approaches was examined for the identification of protonated N-nitrosamines. Quantum chemical calculations were employed to explore feasible mechanisms for the observed reactions.…”
Section: ■ Introductionmentioning
confidence: 99%